Rede de interações de aves-plantas: frugivoria em áreas urbanas da Mata Atlântica - Silva, Thays Almeida (Universidade Federal de São Carlos, 2021)
Urbanization poses countless disturbances to biodiversity, reducing environmental heterogeneity, causing the process of community simplification and favoring species with greater tolerance to anthropogenic actions, mostly generalists in habitats, and eating habits. The interactions between plants and frugivores establish an important structure for a community, and its loss can compromise the species involved and the ecological functions they perform. Thus, interaction networks are important tools to understand ecological processes and patterns responsible for the structural complexity of communities. Although many large urban centers are within the domain of the Atlantic Forest, there are few studies on interaction networks in this environment. Therefore, the study objectives are (1) to characterize this knowledge about frugivory by birds in urban areas of the Atlantic Forest biome; (2) to analyze an interaction between urban birdlife and plants through an interaction network; (3) to verify the behavior of the network and (4) evaluate the influence of exotic species on the network. For this, a bibliographic review on frugivory by birds in urban environments of the Atlantic Forest in Brazil was carried out, articles that included these interactions were surveyed. After the data collection, a list of bird species that consumed fruits is generated, thus creating a binary matrix of plant and bird interactions, which was used for plotting the network, analyzing its structure and organization. For the network, the species connectivity was observed, and the network nesting, estimated with the Nestedness Metric Based on Overlap and Decreasing Fill (NODF). A total of 19 studies in 9 states within the Atlantic Forest were included in the analysis, having generated 78 bird species consuming fruits of 103 plant species. The interaction network has a nested pattern (NODF = 26, p = 0) and 541 interactions were observed, presenting low connectivity (6.65%) which estimates the proportion of the interactions performed in relation to the total of possible interactions. Birds and plant assemblages proved to be stable and resistant in the interaction functioning since the nested structure is a property that demonstration groupings not at random. The number of interactions seems to justify the connectivity, since it decreases due to the network size, reducing the transmission of disturbances. Thus, fruit consumption in urban areas occurs opportunistically, especially by generalist species.
Interactions network of birds and plants: frugivory in urban areas of the Atlantic Forest
Keywords: Redes Ecológicas; Avifauna; Ambiente urbano; CIENCIAS BIOLOGICAS::ECOLOGIA